2010
DOI: 10.1021/la1032916
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Oxygen Evolution in Mesoporous Silica Material: Adsorption of Photosystem II Reaction Center Complex into 23 nm Nanopores in SBA

Abstract: An oxygen-evolving photosynthetic reaction center complex (PSII) was adsorbed into nanopores in SBA, a mesoporous silica compound. We purified the dimer of PSII complex from a thermophilic cyanobacterium, Thermosynechococcus vulcanus, which grows optimally at 57 °C. The thermally stable PSII dimeric complex has a diameter of 20 nm and a molecular mass of 756 kDa and binds more than 60 chlorophylls. The SBA particles, with average internal pore diameters of 15 nm (SBA(15)) and 23 nm (SBA(23)), adsorbed 4.7 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 44 publications
4
63
0
2
Order By: Relevance
“…9,58 Despite such beneficial properties of mesostructured oxides, only a few types of membrane proteins, such as the light-harvesting photosynthetic complexes of the bacterium Thermochratium tepidum , have been incorporated in active forms into them, which has generally been achieved by the post-synthetic adsorption of proteins onto powders of these materials. 9,58,59 These approaches, however, lead to particles that often have composition gradients of proteins, small sizes (<10 µm diameters), and low inter-particle connectivities, which limit the usefulness of powders in exploiting the molecular or ion transport properties of membrane proteins over macroscopic length scales.…”
Section: Introductionmentioning
confidence: 99%
“…9,58 Despite such beneficial properties of mesostructured oxides, only a few types of membrane proteins, such as the light-harvesting photosynthetic complexes of the bacterium Thermochratium tepidum , have been incorporated in active forms into them, which has generally been achieved by the post-synthetic adsorption of proteins onto powders of these materials. 9,58,59 These approaches, however, lead to particles that often have composition gradients of proteins, small sizes (<10 µm diameters), and low inter-particle connectivities, which limit the usefulness of powders in exploiting the molecular or ion transport properties of membrane proteins over macroscopic length scales.…”
Section: Introductionmentioning
confidence: 99%
“…SWCNTs also allowed the transmission of signal molecules such as nitric oxide by plants . Noji et al reported that photosynthetic oxygen‐evolving reaction was achieved with a stable activity when a nanomesoporous silica compound was bound to photosystem II (PSII) . The application of nanosilica enhanced the synthesis of chlorophylls and the activity of carbonic anhydrase .…”
Section: Np Effects On Plant Growth and Mechanism Of Actionmentioning
confidence: 99%
“…A nano mesoporous silica compound (SBA) bound with photosystem II increases the activity of photosynthetic oxygen evolving reactions (Noji et al, 2011). It has also been shown that metal nanoparticles can increase the efficiency of chemical energy production in photosynthetic systems (Govorov et al, 2007).…”
Section: Role Of Nanoparticles In Photosynthesismentioning
confidence: 99%
“…Also, Noji and co-workers (2011) reported that a nano mesoporous silica compound (SBA) bound with photosystem II (PSII) induced stable activity in a photosynthetic oxygen-evolving reaction, indicating the light-driven electron transport from water to the quinone molecules. The authors suggested that PSII-SBA conjugates might have suitable properties as photosensors and artificial photosynthetic systems (Noji et al, 2011). Recently, Lin and co-workers (2014) developed genetically engineered tobacco plants by replacing the RuBisCO gene with 2 genes encoding the large and small subunits of the Se7942 enzyme form cyanobacterium Synechococcus elongatus (Lin et al, 2014).…”
Section: Role Of Nanoparticles In Photosynthesismentioning
confidence: 99%